Answer :
Answer:
[f(2) - f(-1)]/3
Step-by-step explanation:
The table is incomplete, so I will answer the question in general terms. The rate of change between f(-1) and f(2) is computed as follows:
rate of change = [f(2) - f(-1)]/[2 - (-1)] = [f(2) - f(-1)]/3
To complete the calculation you need to replace the values of the function at x = 2 and x = -1, and compute the result.
Answer:
7 over 12
Step-by-step explanation:
The table is incomplete, so I will answer the question in general terms. The rate of change between f(-1) and f(2) is computed as follows:
rate of change = [f(2) - f(-1)]/[2 - (-1)] = [f(2) - f(-1)]/3
To complete the calculation you need to replace the values of the function at x = 2 and x = -1, and compute the result.